Seismic activity on the territory of Slovakia in 2018 - KYSEL, Róbert; CIPCIAR, Andrej; CSICSAY, Kristián; FOJTÍKOVÁ, Lucia; ŠUGÁR, Martin; KRISTEK, Jozef (Contributions to Geophysics and Geodesy, 2019)
The National Network of Seismic Stations of Slovakia (NNSS) consists of eight short period and five broadband permanent seismic stations and a data centre located at the Earth Science Institute of the Slovak Academy of Sciences (ESI SAS). The NNSS recorded and detected 11704 seismic events from all epicentral distances in 2018. Totally 86 earthquakes originated in the territory of Slovakia in 2018. This paper provides basic information on the configuration of the NNSS, routine data processing, seismic activity on the territory of Slovakia in 2018 as well as macroseismic observations collected in 2018.